Fire hazards in industry - Thomson, Norman (Butterworth-Heinemann, 2002)
Significant loss to business occurs through fires in the workplace. Whether large or small, fire causes personal suffering, damage to plant, equipment and buildings, and loss of business. Fire legislation has changed over the past few years, especially with the introduction of European Directives. New regulations mean that employers have to carry out fire risk assessment and then, as a result of their findings, put in place control measures to prevent loss of life. Fire Hazards in Industry has been designed to cover, in general terms, exactly what is required of employers. It is written in simple language and considers the basics of good fire safety management. After reading Fire Hazards in Industry, any employer, safety professional or fire safety officer should be able to install a system for carrying out fire risk assessment.
Includes index
Includes bibliographical references and index
Keywords: LAW / Administrative Law & Regulatory Practice; Fire prevention / Law and legislation; Fire prevention / Management; Fire risk assessment; Fire prevention -- Law and legislation; Fire prevention -- Management